Composite sodium ferric phosphate positive electrode material and preparation method and application thereof

By regulating the stoichiometric ratio of Na, Fe, and P and introducing carbon sources or metal heteroatoms, the problems of difficult synthesis of composite sodium iron phosphate positive electrode materials in high-purity crystal phases, poor conductivity, low specific capacity and short cycle life are solved, and materials with high purity, excellent conductivity and long cycle life are achieved.

CN119905548APending Publication Date: 2025-04-29GUIZHOU DALONG HUICHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878739.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In practical applications, the existing composite sodium ferrophosphate positive electrode materials have problems such as difficulty in synthesis of high-purity crystal phases, poor conductivity, low specific capacity and short cycle life.

Method used

By finely controlling the stoichiometric ratio of Na, Fe, and P, sodium-rich phosphorus-rich composite sodium ferrophosphate was prepared, and the conductive properties were improved by introducing different carbon sources or introducing metal heteroatoms.

Benefits of technology

It significantly improves the crystal phase purity, improves the specific capacity and cycle life of the material, and improves the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905548A_ABST
    Figure CN119905548A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sodium ferric phosphate positive electrode material and a preparation method and application thereof. The chemical formula of the composite sodium ferric phosphate positive electrode material is Na < 4 + x > Fe < 3-y > M < z > (PO4) 2P2 + tO7 / C, x is more than 0 and less than or equal to 1, y is more than or equal to 0.01 and less than 3, z is more than or equal to 0 and less than or equal to 0.5, t is more than 0 and less than or equal to 0.5, and 3-y + z is more than 0 and less than 3, M comprises one or more of Al, Ti, V, Cr and Mn, and C is a carbon coating layer coating the outer layer. Na-rich and P-rich composite sodium ferric phosphate is prepared by adjusting the stoichiometric ratio of Na, Fe and P in the chemical formula, the sodium-rich and phosphorus-rich composite sodium ferric phosphate can effectively inhibit generation of impure phases, and the crystalline phase purity of the sodium-rich and phosphorus-rich composite sodium ferric phosphate is remarkably improved. In addition, the conductivity of the composite material is further improved through carbon coating and metal element doping, and the composite material of the composite sodium ferric phosphate and carbon with a high-purity crystalline phase and high conductivity is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion battery polyanion type positive electrode materials, and in particular relates to a composite sodium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are abundant in resources and low in price. They have important economic value and strategic significance for solving the current situation of my country's high dependence on foreign lithium resources. In addition, compared with the current mainstream lead-acid batteries, sodium-ion batteries have the advantages of high energy density, long cycle life, and excellent low-temperature performance, making them an ideal substitute for lead-acid batteries. Sodium-ion batteries also have price advantages over lithium-ion batteries and are environmentally friendly. Therefore, the development of sodium-ion batteries is of great significance for solving the energy crisis. Sodium-ion battery polyanion positive electrode materials have the advantages of long cycle life, high theoretical capacity, and excellent stability, and are currently being used as the main research and development direction by many companies.

[0003] Iron-based polyanion cathode material composite sodium iron phosphate (Na4Fe3(PO4)2P2O7, abbreviated as NFPP) has the advantages of both phosphate and pyrophosphate, high specific capacity, long cycle life, and environmental friendliness, and is one of the most promising cathode materials for sodium ion batteries. However, in actual application, NFPP materials have difficulties in synthesizing high-purity crystal phases, poor conductivity, low specific capacity, and short cycle life. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, provide a composite sodium iron phosphate positive electrode material and a preparation method and application thereof, and improve the crystal phase purity, conductivity and cycle life.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A composite sodium iron phosphate positive electrode material, the chemical formula of the composite sodium iron phosphate positive electrode material is Na 4+x Fe 3-y M z (PO4)2P 2+t O7 / C, wherein 0<x≤1, 0.01≤y<3, 0≤z≤0.5, 0<t≤0.5 and 0<3-y+z<3, M includes one or more of Al, Ti, V, Cr, and Mn, and the C is a carbon coating layer coated on the outer layer.

[0006] As a further improvement, 0.1≤x≤0.3, 0.1≤t≤0.2.

[0007] As a further improvement, wherein M is Al, 0.08≤z≤0.2; and / or The C content is 1-5wt% of the material mass.

[0008] The present invention also provides a method for preparing the composite sodium iron phosphate positive electrode material, comprising the following steps: S1. dispersing a carbon source, an iron source, a phosphorus source, a sodium source and a doping metal source in water and grinding them to prepare a mixed suspension; S2. The mixed suspension obtained in S1 was spray dried to obtain a powder; S3. The powder obtained in S2 is pre-annealed, and then high-temperature annealed to obtain a composite sodium iron phosphate positive electrode material.

[0009] As a further improvement, the carbon source is one or more of glucose, lactose, starch, gelatin, chitosan, cyclodextrin, polyvinyl alcohol, polyvinyl pyrrolidone, or citric acid.

[0010] As a further improvement, the carbon source is citric acid and chitosan.

[0011] As a further improvement, the average particle size of S1 after grinding is 50-500 nm.

[0012] As a further improvement, S3: the pre-annealing temperature is 150-450°C, and the heating rate is 0.5-15°C / min; and / or The high temperature annealing temperature in S3 is 500-750°C, and the heating rate is 0.5-15°C / min.

[0013] The present invention also provides a sodium ion battery positive electrode plate, which comprises the composite sodium iron phosphate positive electrode material or the composite sodium iron phosphate positive electrode material prepared by the method.

[0014] The present invention also provides a sodium ion battery, which comprises the sodium ion battery positive electrode plate.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention obtains a sodium-rich and phosphorus-rich composite sodium iron phosphate. During the research process, the applicant found that by finely controlling the stoichiometric ratio of Na, Fe, and P in the chemical formula to prepare a Na-rich and P-rich composite sodium iron phosphate, the generation of electrochemically inactive impurities can be effectively suppressed, the crystal phase purity is significantly improved, and the specific capacity and cycle life of the material are improved. In addition, the introduction of different carbon sources for coating or the introduction of metal heteroatoms for doping can effectively improve its conductivity. Through these two improvements, the rate performance and cycle life of the NFPP material are effectively improved.

[0016] The preparation method of the present invention is simple, the process route is compatible with current mainstream positive electrode synthesis equipment, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 This is the X-ray diffraction pattern of the sodium-rich and phosphorus-rich composite sodium iron phosphate positive electrode material obtained in Example 1.

[0019] Figure 2 This is a scanning electron microscope image of the sodium-rich and phosphorus-rich composite sodium iron phosphate positive electrode material obtained in Example 2.

[0020] Figure 3 This is a charge and discharge curve diagram of the sodium-rich and phosphorus-rich composite sodium iron phosphate positive electrode material obtained in Example 3.

[0021] Figure 4 This is the X-ray diffraction pattern of the composite sodium iron phosphate positive electrode material obtained in Comparative Example 1.

[0022] Figure 5 This is the X-ray diffraction pattern of the composite sodium iron phosphate positive electrode material obtained in Comparative Example 2. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0024] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0026] The composite sodium iron phosphate positive electrode material of the present invention has a chemical formula of Na 4+x Fe 3-y M z (PO4)2P 2+t O7 / C, wherein 0<x≤1, 0.01≤y<3, 0≤z≤0.5, 0<t≤0.5 and 0<3-y+z<3, M is a doped metal, including one or more of Al, Ti, V, Cr, and Mn, and C is a carbon coating layer coated on the outer layer. The carbon content is any value between 1-5wt%, and the total weight of the material is 100%.

[0027] The composite sodium iron phosphate of the present invention is a sodium-rich and phosphorus-rich structure, satisfying 0<x≤1, 0<t≤0.5, more preferably, 0.1≤x≤0.3, 0.1≤t≤0.2, and more preferably, 0.1≤y≤0.2.

[0028] Appropriate metal doping can effectively inhibit the formation of impurity phases, improve the purity of the crystal phase, and improve the rate performance and cycle stability of the sample (refer to Example 3). M is preferably Al, and preferably, 0.08≤z≤0.2.

[0029] The composite sodium iron phosphate positive electrode material of the present invention has a high-purity crystalline phase and high conductivity. Studies have found that the element ratio of sodium and phosphorus has an important influence on the purity of the crystalline phase and the electrochemical performance. If the sodium and phosphorus ratio is too low, there will be too many impurities, which will aggravate the problem of poor electronic conductivity and affect the rate performance of the material; if the sodium and phosphorus ratio is too high, it will affect the stability of the overall structure of NFPP, resulting in structural collapse and adverse phase changes during the charge and discharge process, and even the inability to generate a composite sodium iron phosphate material. The appropriate sodium-phosphorus ratio can effectively inhibit the generation of impurities and improve the purity of the crystalline phase and the electrochemical performance. The sodium and phosphorus ratio is within the scope of the present invention and has excellent conductivity, rate performance and cycle life.

[0030] In some embodiments, the average particle size of the composite sodium iron phosphate positive electrode material of the present invention is preferably 2-8.5 μm, more preferably 4-8.5 μm.

[0031] In some embodiments, the composite sodium iron phosphate positive electrode material of the present invention is prepared by a sand milling-spray drying-pre-annealing-high temperature annealing process, which specifically includes the following steps: S1. Disperse a carbon source, an iron source, a phosphorus source, a sodium source, and a doping metal source in water and grind them to prepare a mixed suspension.

[0032] In some embodiments, the carbon source is one or a mixture of glucose, lactose, starch, gelatin, chitosan, cyclodextrin, polyvinyl alcohol, polyvinyl pyrrolidone, citric acid, preferably starch. The carbon source accounts for 0.5%-12wt% of the total mass of the raw material, preferably 3wt%.

[0033] The selection of a suitable carbon source can improve the sand milling efficiency and effectively reduce the particle size of the spray-dried sample powder. For example, Example 2 of the present invention uses two carbon sources (citric acid + chitosan, mass ratio 4:1) for coating. Compared with using one carbon source, it effectively reduces the viscosity of the suspension, improves the grinding efficiency, and can significantly reduce the particle size of the spray-dried sample powder, reducing the particle size of the positive electrode material. The average particle size of the composite sodium iron phosphate positive electrode material of the present invention can be controlled at 2-8.5μm, more preferably 4-8.5μm. The reasonable distribution of particle size will affect the rate performance and compaction density of the battery. Too large a particle size will lead to poor battery rate performance and short cycle life.

[0034] In some embodiments, the iron source is one of ferrous oxalate, ferrous phosphate, ferrous hydroxide, ferrous sulfate, ferric nitrate, ferric acetylacetonate, or a mixture thereof, preferably ferrous oxalate.

[0035] In some embodiments, the phosphorus source is one or a mixture of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, diamine hydrogen phosphate, metaphosphoric acid, and hypophosphorous acid, preferably phosphoric acid.

[0036] In some embodiments, the sodium source is one or a mixture of sodium chloride, sodium oxalate, sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, sodium acetate, sodium ethoxide, sodium oleate, sodium pyrophosphate, preferably sodium bicarbonate.

[0037] In some embodiments, the doping metal source is one of aluminum nitrate nonahydrate, aluminum oxide, aluminum hydroxide, or a mixture thereof.

[0038] In some embodiments, the carbon source, iron source, phosphorus source, sodium source, and doped metal source are dispersed in water and then stirred for 1-5 hours, preferably 3 hours. The mixed solution is then put into a sand mill and sanded to obtain a mixed suspension, and the sanding time is 1-5 hours, preferably 2-3 hours. The average particle size after sanding is 50-500 nm, preferably 250 nm.

[0039] S2. The obtained mixed suspension is spray-dried to obtain a powder.

[0040] In some embodiments, the spray drying air inlet temperature is 100-300° C., preferably 200° C., and the air outlet temperature is 60-150° C., preferably 120° C. The spray drying needle passing frequency is 2-20 times / second, and preferably 5 times / second.

[0041] S3. The obtained powder is pre-annealed and then high-temperature annealed to obtain a composite sodium iron phosphate positive electrode material.

[0042] In some embodiments, the pre-annealing temperature is 150-450°C, preferably 300°C; the heating rate is 0.5-15°C / min, preferably 5°C / min; the holding time is 1-15h, preferably 8h. The pre-annealing atmosphere is one or a mixture of air, argon, nitrogen, and ammonia. After pre-annealing, the temperature can be naturally cooled to room temperature. Appropriate pre-annealing treatment is conducive to forming a more stable structure, thereby improving the structural and chemical stability of the material.

[0043] In some embodiments, the high temperature annealing temperature is 500-750°C, preferably 600°C; the heating rate is 0.5-15°C / min, preferably 5°C / min; the holding time is 1-15h, preferably 15h. The annealing atmosphere is one or a mixture of air, argon, nitrogen, and ammonia. After annealing, the temperature can be naturally cooled to room temperature.

[0044] The speed of the heating rate during the annealing process has an important influence on the crystallinity, phase composition, electrochemical properties and practical application performance of the positive electrode material. A faster heating rate helps to maintain the structural integrity of the material and improve the electrochemical performance, but it may also cause particle breakage; while a slower heating rate may lead to the formation of impurity phases and a decrease in material performance. Therefore, the appropriate heating rate selection of the present invention is based on a comprehensive consideration of material performance requirements and preparation costs.

[0045] In some embodiments, the method for preparing a positive electrode sheet for a sodium ion battery comprises the following steps: The composite sodium iron phosphate positive electrode material, conductive agent and binder are dispersed in a solvent, coated on aluminum foil, and then dried to obtain a sodium ion battery positive electrode sheet.

[0046] In some embodiments, the mass ratio of the composite sodium iron phosphate positive electrode material, the conductive agent, and the binder is (8-9.5): (0.2-1): (0.2-1), and the optimal ratio is 8:1:1. The conductive agent is one or a mixture of carbon black, conductive graphite, carbon nanotubes, and nano-carbon fibers. The binder is one or a mixture of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyvinyl alcohol (PVA), sodium alginate (Alg), and polytetrafluoroethylene (PTFE), and the optimal ratio is polyvinylidene fluoride (PVDF).

[0047] In some embodiments, the composite sodium iron phosphate positive electrode material, the conductive agent, and the binder are dispersed in a solvent (eg, N-methylpyrrolidone), stirred for 10-15 hours, and then vacuum dried at 90-110° C. for 10-15 hours.

[0048] Example 1 Preparation of Na 4.2 Fe 2.89 (PO4)2P 2.1 O7 / C composite material (x=0.2, y=0.11, z=0, t=0.1, C content 3.2%) Pour 300 g of ferric phosphate, 152.5 g of sodium dihydrogen phosphate, 47.2 g of sodium carbonate, and 60 g of citric acid into a 2000 ml beaker, add 1500 ml of water and stir for 2 h to obtain a uniformly mixed dispersion.

[0049] The above dispersion was added into a nano sand mill and ground for 3 h to obtain a mixed solution with an average particle size of 200 nm.

[0050] The above solution was spray dried, the air inlet temperature of the spray dryer was 200°C, the air outlet temperature was 100°C, and the needle passing frequency was 10 times / second. After the spray drying was completed, the powder sample was collected.

[0051] The powder sample was pre-annealed at a temperature of 280° C., a holding time of 8 h, a heating rate of 5° C. / min, and an annealing atmosphere of argon to obtain a pre-annealed sample.

[0052] The pre-annealed sample was subjected to high temperature annealing at 580°C, holding time of 15 h, heating rate of 5°C / min, and annealing atmosphere of argon to obtain the target sample (Na 4.2 Fe 2.89 (PO4)2P 2.1 O7 / C).

[0053] Take 80 mg of the target sample, 10 mg of conductive carbon black, and 10 mg of PVDF and disperse them in 0.8 g of N-methylpyrrolidone solution. After stirring for 12 hours, coat them on aluminum foil and vacuum dry them at 100°C for 10 hours to obtain the positive electrode sheet of the sodium ion battery.

[0054] Example 2 Preparation of Na 4.3 Fe 2.85 (PO4)2P 2.2 O7 / C composite material (x=0.3, y=0.15, z=0, t=0.2, C content 2.8%) Pour 300 g of ferric phosphate, 164 g of sodium dihydrogen phosphate, 48.5 g of sodium carbonate, 40 g of citric acid, and 10 g of water-soluble chitosan into a 2000 ml beaker, add 1500 ml of water and stir for 3 h to obtain a uniformly mixed dispersion.

[0055] The above dispersion was added into a nano sand mill and ground for 4 h to obtain a mixed solution with an average particle size of 150 nm.

[0056] The above solution was spray dried, the air inlet temperature of the spray dryer was 250°C, the air outlet temperature was 120°C, and the needle passing frequency was 10 times / second. After the spray drying was completed, the powder sample was collected.

[0057] The powder sample was pre-annealed at a temperature of 300° C., a holding time of 5 h, a heating rate of 5° C. / min, and an annealing atmosphere of argon to obtain a pre-annealed sample.

[0058] The pre-annealed sample was subjected to high temperature annealing at 600 °C, holding time of 8 h, heating rate of 5 °C / min, and annealing atmosphere of argon to obtain the target sample (Na 4.3 Fe 2.85 (PO4)2P 2.3 O7 / C). Figure 2 This is a scanning electron microscope image of the sodium-rich and phosphorus-rich composite sodium iron phosphate composite material obtained in Example 2.

[0059] Take 85 mg of the target sample, 10 mg of conductive carbon black, and 5 mg of PVDF and disperse them in 0.8 g of N-methylpyrrolidone solution. After stirring for 12 hours, coat them on aluminum foil and dry them in vacuum at 120°C for 10 hours to obtain the positive electrode sheet of the sodium ion battery.

[0060] Example 3 Preparation of Na 4.1 Fe 2.85 Al 0.1 (PO4)2P 2.1 O7 / C composite material (x=0.1, y=0.15, z=0.1, t=0.1, C content 3.7%) Pour 200 g of ferrous oxalate, 114.6 g of sodium pyrophosphate, 96 g of ammonium dihydrogen phosphate, 12.2 g of aluminum nitrate nonahydrate, and 50 g of glucose into a 2000 ml beaker, add 1500 ml of water and stir for 3 h to obtain a uniformly mixed dispersion.

[0061] The above dispersion was added into a nano sand mill and ground for 3 h to obtain a mixed solution with an average particle size of 200 nm.

[0062] The above solution was spray dried, the air inlet temperature of the spray dryer was 180°C, the air outlet temperature was 96°C, and the needle passing frequency was 5 times / second. After the spray drying was completed, the powder sample was collected.

[0063] The powder sample was pre-annealed at a temperature of 350° C., a holding time of 5 h, a heating rate of 5° C. / min, and an annealing atmosphere of argon to obtain a pre-annealed sample.

[0064] The pre-annealed sample was subjected to high temperature annealing at 500 °C, holding time of 15 h, heating rate of 5 °C / min, and annealing atmosphere of argon to obtain the target sample (Na 4.1 Fe 2.85 Al 0.1 (PO4)2P 2.1 O7 / C).

[0065] 80 mg of the target sample, 15 mg of conductive carbon black, and 5 mg of PVDF were dispersed in 0.8 g of N-methylpyrrolidone solution, stirred for 12 h, coated on aluminum foil, and vacuum dried at 110 °C for 12 h to obtain the positive electrode sheet of the sodium ion battery.

[0066] Comparative Example 1 Preparation of Na4Fe3(PO4)P2O7 / C composite material (x=0, y=0, z=0, t=0, sodium-phosphorus ratio is too low) Pour 200 g of ferrous oxalate, 98 g of sodium pyrophosphate, 85.1 g of diammonium phosphate, and 37 g of citric acid into a 2000 ml beaker, add 1200 ml of water and stir for 3 h to obtain a uniformly mixed dispersion.

[0067] The above dispersion was added into a nano sand mill and ground for 3 h to obtain a mixed solution with an average particle size of 300 nm.

[0068] The above solution was spray dried, the air inlet temperature of the spray dryer was 200°C, the air outlet temperature was 105°C, and the needle passing frequency was 5 times / second. After the spray drying was completed, the powder sample was collected.

[0069] The powder sample was pre-annealed at a temperature of 350° C., a holding time of 8 h, a heating rate of 5° C. / min, and an annealing atmosphere of argon to obtain a pre-annealed sample.

[0070] The pre-annealed sample was subjected to high temperature annealing at a temperature of 550°C, a holding time of 20 h, a heating rate of 5°C / min, and an annealing atmosphere of argon to obtain the target sample (Na4Fe3(PO4)P2O7 / C).

[0071] 80 mg of the target sample, 15 mg of conductive carbon black, and 5 mg of PVDF were dispersed in 0.8 g of N-methylpyrrolidone solution, stirred for 12 h, coated on aluminum foil, and vacuum dried at 110 °C for 12 h to obtain the positive electrode sheet of the sodium ion battery.

[0072] Comparative Example 2 Na 5.5 Fe3(PO4)2P 2.8 O7 / C composite material (x=1.5, t=0.8, y=0, z=0, sodium-phosphorus ratio is too high) Pour 300 g of ferrous oxalate, 157 g of sodium pyrophosphate, 121.6 g of diammonium phosphate, and 50 g of sucrose into a 2000 ml beaker, add 1500 ml of water and stir for 3 h to obtain a uniformly mixed dispersion.

[0073] The above dispersion was added into a nano sand mill and ground for 3 h to obtain a mixed solution with an average particle size of 300 nm.

[0074] The above solution was spray dried, the air inlet temperature of the spray dryer was 190°C, the air outlet temperature was 100°C, and the needle passing frequency was 5 times / second. After the spray drying was completed, the powder sample was collected.

[0075] The powder sample was pre-annealed at a temperature of 300° C., a holding time of 8 h, a heating rate of 5° C. / min, and an annealing atmosphere of argon to obtain a pre-annealed sample.

[0076] The pre-annealed sample was subjected to high temperature annealing at 500 °C, holding time of 15 h, heating rate of 5 °C / min, and annealing atmosphere of argon to obtain the target sample (Na 5.5 Fe3(PO4)2P 2.8 O7 / C).

[0077] 80 mg of the target sample, 10 mg of conductive carbon black, and 10 mg of PVDF were dispersed in 0.8 g of N-methylpyrrolidone solution, stirred for 12 h, coated on aluminum foil, and vacuum dried at 100 °C for 12 h to obtain the positive electrode sheet of the sodium ion battery.

[0078] Figure 1 This is the X-ray diffraction pattern of the sodium-rich and phosphorus-rich composite sodium iron phosphate composite material obtained in Example 1. Figure 4 The X-ray diffraction diagram of the composite sodium iron phosphate composite material prepared in Comparative Example 1 when the sodium-phosphorus ratio is lower than that of the present invention shows that there are more impurities. The results show that the purity of the sample is low and there are more impurities when the sodium-phosphorus ratio is lower than that of the present invention. Figure 5 This is the X-ray diffraction diagram of the composite sodium iron phosphate composite material prepared in Comparative Example 2 when the sodium-phosphorus ratio is higher than that of the present invention. The results show that the composite sodium iron phosphate sample cannot be normally synthesized when the sodium-phosphorus ratio is higher than that of the present invention.

[0079] Figure 1 , 4 5. The comparison shows that the high-purity crystal form can only be synthesized when the sodium-phosphorus ratio in the composite sodium iron phosphate is within the ratio of the present invention. Too low sodium-phosphorus content leads to too many impurities, and too high sodium-phosphorus ratio cannot generate composite sodium iron phosphate materials. The comparison results show that by regulating the sodium-phosphorus ratio, achieving sodium-rich and phosphorus-rich can effectively inhibit the generation of electrochemically inactive impurities and improve the purity of the crystal phase.

[0080] The button cells of Examples 1-3 and Comparative Examples 1-2 were assembled and the electrochemical performance was tested (1C=129 mAh / g). The metal sodium sheet was used as the negative electrode, and the electrolyte was 1 mol / L NaClO4 dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) solvents with a volume ratio of 1:1. The test environment was room temperature. Figure 3 This is a charge and discharge curve diagram of the sodium-rich and phosphorus-rich composite sodium iron phosphate composite material obtained in Example 3.

[0081] The particle sizes of the samples of Examples 1-3 and Comparative Examples 1-2 were measured using a laser particle size analyzer.

[0082] The electrochemical performance test and particle size statistics results of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.

[0083] Table 1 Electrochemical performance and particle size test data of each embodiment and comparative example

[0084] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A composite sodium iron phosphate positive electrode material, characterized in that: The chemical formula of the composite sodium iron phosphate positive electrode material is Na 4+x Fe 3-y M z (PO4)2P 2+t O7 / C, wherein 0<x≤1, 0.01≤y<3, 0≤z≤0.5, 0<t≤0.5 and 0<3-y+z<3, M includes one or more of Al, Ti, V, Cr, and Mn, and the C is a carbon coating layer coated on the outer layer.

2. The composite sodium iron phosphate positive electrode material according to claim 1, characterized in that Among them, 0.1≤x≤0.3, 0.1≤t≤0.

2.

3. The composite sodium iron phosphate positive electrode material according to claim 1, characterized in that wherein M is Al, 0.08≤z≤0.2; and / or The C content is 1-5wt% of the material mass.

4. A method for preparing the composite sodium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1. dispersing a carbon source, an iron source, a phosphorus source, a sodium source and a doping metal source in water and grinding them to prepare a mixed suspension; S2. The mixed suspension obtained in S1 was spray dried to obtain a powder; S3. The powder obtained in S2 is pre-annealed, and then high-temperature annealed to obtain a composite sodium iron phosphate positive electrode material.

5. The preparation method according to claim 4, characterized in that: The carbon source is one or more of glucose, lactose, starch, gelatin, chitosan, cyclodextrin, polyvinyl alcohol, polyvinyl pyrrolidone, or citric acid.

6. The preparation method according to claim 5, characterized in that: The carbon sources are citric acid and chitosan.

7. The preparation method according to claim 4, characterized in that The average particle size of S1 after grinding is 50-500 nm.

8. The preparation method according to claim 4, characterized in that S3: the pre-annealing temperature is 150-450°C, and the heating rate is 0.5-15°C / min; and / or The high temperature annealing temperature in S3 is 500-750°C, and the heating rate is 0.5-15°C / min.

9. A positive electrode plate for a sodium ion battery, characterized in that: It comprises the composite sodium iron phosphate positive electrode material according to any one of claims 1 to 3 or the composite sodium iron phosphate positive electrode material prepared by the method according to any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: It includes the sodium ion battery positive electrode plate as described in claim 9.